Dissecting justice: The legal significance of medical records and informed consent in malpractice cases - Darwis, Muhammad (Privietlab, 2026)
This study examines the legal position and strength of medical records and informed consent as evidence in medical malpractice cases in Indonesia. Using normative legal research methods, this study applies a statutory approach and an analytical approach to understand the aspects of health law and related evidentiary law. The study results indicate that medical records have a strong position as written evidence in civil procedural law and as written evidence in criminal procedural law. Meanwhile, informed consent plays an important role in proving the fulfilment of the doctor's obligation to provide information to patients. However, the existence of informed consent does not necessarily eliminate the doctor's responsibility if proven to have committed negligence. This study also reveals that the use of medical records and informed consent as evidence must consider aspects of patient confidentiality and the development of electronic medical record technology. In conclusion, although medical records and informed consent have significant evidentiary power, their use must be carried out carefully by considering the case context, medical professional standards, and applicable health law principles to ensure justice in resolving medical malpractice cases in Indonesia.